2015
DOI: 10.3390/resources4040939
|View full text |Cite
|
Sign up to set email alerts
|

A Standard Characterization Methodology for Respirable Coal Mine Dust Using SEM-EDX

Abstract: A key consideration for responsible development of mineral and energy resources is the well-being of workers. Respirable dust in mining environments represents a serious concern for occupational health. In particular, coal miners can be exposed to a variety of dust characteristics depending on their work activities, and some exposures may pose risk for lung diseases like CWP and silicosis. As underscored by common regulatory frameworks, respirable dust exposures are generally characterized on the basis of tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 16 publications
2
40
0
Order By: Relevance
“…To account for these differences, the atomic percentage limits for the CCSEM routine were gradually refined until automated and manual results agreed across a wide range of individual particles (i.e., between about 1-10 µm, and representing all defined chemical composition categories shown in Table 2). It should also be noted that observations during this process, along with previous observations [27,28], indicated that particles classified in the "mixed carbonaceous" category are most often small and/or thin alumino-silicate particles [27,28]. Therefore, the mixed carbonaceous and alumino-silicate categories have been combined (i.e., to a total alumino-silicate, TAS, category) for reporting CCSEM-EDX results in this paper.…”
Section: Particle Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…To account for these differences, the atomic percentage limits for the CCSEM routine were gradually refined until automated and manual results agreed across a wide range of individual particles (i.e., between about 1-10 µm, and representing all defined chemical composition categories shown in Table 2). It should also be noted that observations during this process, along with previous observations [27,28], indicated that particles classified in the "mixed carbonaceous" category are most often small and/or thin alumino-silicate particles [27,28]. Therefore, the mixed carbonaceous and alumino-silicate categories have been combined (i.e., to a total alumino-silicate, TAS, category) for reporting CCSEM-EDX results in this paper.…”
Section: Particle Characteristicsmentioning
confidence: 99%
“…Regarding particle chemistry, the classification criteria for the CCSEM-EDX routine were adapted from those previously reported for the manual routine [28]. In that earlier work, detailed manual SEM-EDX analysis of respirable dust samples representative of Appalachian coal mines was used to define six distinct classification categories: carbonaceous, mixed carbonaceous, alumino-silicate, quartz, carbonate, and heavy mineral.…”
Section: Particle Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations